Building a load characteristic of the fuel injection system of a ship’s medium-speed engine diesel in dynamic tests conditions - Polovinka, Edward; Slobodianiuk, Nikolay (Technology audit and production reserves, 2018)
The object of research in the work is hydrodynamic processes in the high pressure fuel system of the ship’s medium-speed engine on variable modes. Variable regimes constitute a significant part of the operational time of a number of types of ships (tugs, fishing vessels, etc.), and for transport fleets they are characteristic for maneuvering. In the latter case, reliability and environmental safety for sanitary control zones are of particular importance. Studies of fuel supply processes in variable modes are important, since they largely determine all the operating characteristics of a diesel engine and are not well studied The article presents an experiment in which the task is obtaining the load characteristics and the study of transients in the fuel equipment of the ship’s medium-speed diesel engine under dynamic testing conditions. In the course of the research, a developed hardware and software complex is used to ensure the implementation of the experiment plan, fixation, processing and oscillography of the obtained data. An electromechanical system is developed by rack displacement of a high-pressure fuel pump with programmed computer control. The experiment program provides for changing the rack position in the whole range covering the operational load characteristic. The discrete displacement includes five fixed rack positions with a step transition between them. During testing, the high-pressure fuel pump completes 80 injection cycles over 44 s. The transition time between the individual fixed positions of the racks is 0.44 s. The stabilization period of hydrodynamic processes in the fuel supply system is close to 0.22 s. In the investigated range of rack positions mr=25–5 mm the main parameters of the fuel injection are as follows: рn.с=474–232 bar; рn.i=457–222 bar; рp=445–162 bar. The possibility of obtaining load characteristics by dynamic tests is shown, which significantly reduces the test time and increases the reliability of the data, eliminating the influence of the time trend parameters.